PARTISIPASI MASYARAKAT DALAM MEWUJUDKAN KOTA LAYAK ANAK DI KOTA SURAKARTA - Wulandari, Anjani; Taufiq, Achmad (Journal of Politic and Government Studies, 2019)
Attempt to realize a child friendly city need community participation inparticipating in every policy that protects children's rights, communityparticipation is very important to know what they need to improve children'swelfare and development. Communities are given space to participate and channelideas and aspirations in child worthy programs. In this regard, the Surakarta citygovernment asked the community to participate in achieving success and careabout the children's issues needed by the children of Surakarta City in Realizing aChild Friendly City. this is focused on communities that have child care such asnon-governmental organizations and children's forums.This study aims to explain how the process of participation and forms ofcommunity participation and obstacles encountered in the implementation ofchild-friendly city policies in Surakarta City. What forms of participation arecarried out by the community. The researcher also wanted to find out how theprocess of community institutions that have concern for children and the Surakartachildren's forum was able to get an award. The research method used isdescriptive qualitative. The technique of collecting data is done by interviews,documentation and literature. Data validity and reliability were tested using thedata source Triangulation technique.The results of these studies are that community participation is realized because ofthe high public awareness of children's rights that must be fulfilled. The enormousenthusiasm of the community successfully delivered the city of Surakarta to thehighest award. The form of community participation is in the form of energy,mind and material. Communities work with movers from the formal and nonformalsectors. From the non-formal sector there are Non GovernmentalOrganizations, the Business World together with the Surakarta Children's Forumalways support and invite the public to be involved in supporting governmentpolicies. From the government itself, it always provides an open space forparticipation to convey the aspirations of the community. The challenge faced bythe city of Surakarta in realizing a city worthy of children is the still highegosectoral inter DPOs in Child-Friendly Cities and the unavailability of a childdata information system in Surakarta.Keywords: Community Participation, Child Friendly City